2021
DOI: 10.1002/adsu.202100420
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Locking of Interfacial Side Reaction Sites Promotes Aluminum‐Air Batteries Close to Theoretical Capacity

Abstract: Aluminum metal has been regarded as a promising anode material for aqueous metal‐air batteries. However, the stable cycling of Al anodes is challenging due to the severe parasitic corrosion of Al metal in alkaline electrolytes. Here, a novel additive, n‐octylphosphonic acid (OPA), is introduced into the typical NaOH electrolyte system to improve the interfacial stability of Al anodes and thus promote high‐performance Al‐air batteries (AABs). Combining several experimental characterizations and theoretical calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that negatively charged O atoms may form chemical bonds with the surface of Al . Herein, 5 ps AIMD simulations were performed to investigate the interaction between HCOO – and Al(111), Al(220) as well as Al(200), because the exposure of these three Al facets was observed in our experiments.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have shown that negatively charged O atoms may form chemical bonds with the surface of Al . Herein, 5 ps AIMD simulations were performed to investigate the interaction between HCOO – and Al(111), Al(220) as well as Al(200), because the exposure of these three Al facets was observed in our experiments.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure 2c, the Al foil after soaking in 4 M NaOH exhibits two peaks at 531.2 and 531.7 eV, corresponding to Al−O (Al 2 O 3 ) and O−H (Al(OH) 3 ), respectively. 25,50 By contrast, the Al foil after soaking in 4 M HCOONa−4 M NaOH presents two other peaks at 535.8 and 530.0 eV, which can be assigned to HCOO − and Al−O−C, respectively (Figure 2d). 48,51 This provides the direct evidence for the existence of HCOO − selfassembled film on the Al surface.…”
Section: Thementioning
confidence: 99%
See 3 more Smart Citations